2010
DOI: 10.1111/j.1600-0501.2010.01986.x
|View full text |Cite
|
Sign up to set email alerts
|

Antral computerized tomography pre-operative evaluation: relationship between mucosal thickening and maxillary sinus function

Abstract: irregular (> 5 mm), circumferential and complete mucosal appearance are associated with an increased risk for sinus outflow obstruction and an ENT consultation is recommended. A rounded mucosal appearance of any grade is associated with a low risk for sinus obstruction. Routine CT scans, including the maxillary sinus ostium, are recommended.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
90
1
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 102 publications
(98 citation statements)
references
References 23 publications
4
90
1
3
Order By: Relevance
“…In our study most of the cases diagnosed as chronic rhinusinusitis have the score between16-20 (35%) and minimum has the score between 21-24 (10%). The findings are consistent with the study done by Silberstein S et al 5 On the basis of mucosal thickening most common pattern noted is circumferential (7%) followed by irregular (2%).This finding is supported by Carmeli G et al 6 Fungal sinusitis is a chronic form of inflammation which shows complete opacification of sinus, bony erosion, and calcification with involved sinus showing higher attenuation than bacterial sinusitis. In our study 6 patients had fungal sinusitis, of which nasal involvement was seen in 16% and bony erosion and calcification seen in 30% and 50% respectively.…”
Section: Figure 10: Classification Of Cases On the Basis Of Nasal Patsupporting
confidence: 82%
“…In our study most of the cases diagnosed as chronic rhinusinusitis have the score between16-20 (35%) and minimum has the score between 21-24 (10%). The findings are consistent with the study done by Silberstein S et al 5 On the basis of mucosal thickening most common pattern noted is circumferential (7%) followed by irregular (2%).This finding is supported by Carmeli G et al 6 Fungal sinusitis is a chronic form of inflammation which shows complete opacification of sinus, bony erosion, and calcification with involved sinus showing higher attenuation than bacterial sinusitis. In our study 6 patients had fungal sinusitis, of which nasal involvement was seen in 16% and bony erosion and calcification seen in 30% and 50% respectively.…”
Section: Figure 10: Classification Of Cases On the Basis Of Nasal Patsupporting
confidence: 82%
“…Incidental findings such as mucosal thickening can be associated with a sinus outflow obstruction which can impact on the clinician’s treatment decisions [6]. This abnormality is frequently investigated in exams for implant treatment planning, but other abnormalities are often overlooked.…”
Section: Discussionmentioning
confidence: 99%
“…Incidental abnormalities of the maxillary sinus are common findings in spiral computed tomography (CT) scans [3-6] and CBCT dental scans [7,8]. In a study by Cha et al, using CBCT examinations, the abnormalities found were signs of acute sinusitis (7.5%), retention cysts (3.5%), and polypoid mucosal thickening (2.3%) [7].…”
Section: Introductionmentioning
confidence: 99%
“…[16] The variations in the results of our study can be attributed to the different imaging modality,[89101114] population addressed in the study,[1522] variation in sample size[1617] and the definition of abnormality, which is considered. [1823242526]…”
Section: Discussionmentioning
confidence: 99%